Oridonin induces apoptosis and autophagy in murine fibrosarcoma L929 cells partly via NO-ERK-p53 positive-feedback loop signaling pathway - Ye Yuan-chao; Wang Hong-ju; Xu Lei; Liu Wei-wei; Liu Bin-bin; Tashiro Shin-Ichi; Onodera Satoshi; Ikejima Takashi (Acta Pharmacologica Sinica; Vol 33, No 8 (August 2012): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the role of nitric oxide (NO) in oridonin-induced apoptosis and autophagy in murine fibrosarcoma L929 cells and the underlying molecular mechanisms. Methods: Cell viability was measured using MTT assay. Intracellular NO level, SubG1 cell ratio and autophagy cell ratios were analyzed with flow cytometry after diaminofluorescein-2 diacetate (DAF-2DA), propidium iodide (PI) and monodansylcadaverine (MDC) staining, respectively. Protein expression was examined using Western blot analysis. Results: Exposure of L929 cells to oridonin (50 μmol/L) for 24 h led to intracellular NO production. Pretreatment with NOS inhibitor 1400w or L-NAME inhibited oridonin-induced apoptosis and autophagy in L929 cells. The pretreatment decreased the apoptosis-related protein Bax translocation and cytochrome c release, increased Bcl-2 level, reversed the autophagy-associated protein Beclin 1 increase and conversion of LC3 I to LC3 II. Furthermore, pretreatment with NO scavenger DTT completely inhibited oridonin-induced apoptosis and autophagy in L929 cells. In addition, oridonin (50 μmol/L) activated ERK and p53 in L929 cells, and the interruption of ERK and p53 activation by PD 98059, pifithrin-α, or ERK siRNA decreased oridonin-induced apoptosis and autophagy. The inhibition of NO production reduced oridonin-induced ERK and p53 activation, and NO production was down-regulated by blocking ERK and p53 activation. Conclusion: NO played a pivotal role in oridonin-induced apoptosis and autophagy in L929 cells. Taken together with our previous finding that ERK contributes to p53 activation, it appears that NO, ERK, and p53 form a positive feedback loop. Consequently, we suggest that oridonin-induced apoptosis and autophagy are modulated by the NO-ERK-p53 molecular signaling mechanism in L929 cells.